Konwencja o ochronie niematerialnego dziedzictwa kulturowego UNESCO w perspektywie dyskursu antropologicznego - Czerwińska, Kinga (Studia Etnologiczne i Antropologiczne, 2012)
In the light of a deepening globalization and degradation of a cultural diversification of societies, many actions aiming at maintaining their unique nature are taken. The very activity concentrates especially on intangible representations of cultural heritage which are particularly susceptible to depreciation, and, consequently, loss as a result of modern civilization processes such as uncontrolled urbanization and destruction of rural areas. The awareness of constantly progressing dangers enforces taking proper actions and engaging the international society. Out of concern for maintaining the most precious elements of the world intangible heritage, a series of programmes, among whom the ones conducted by UNESCO should be paid special attention to. One of them is the Convention for the Safeguarding of the Intangible Cultural Heritage, the result of which is among others creating The Representative List of Intangible Cultural Heritage of Humanity. UNESCO’s convention was approved of enthusiastically as an important step to maintaining cultural heritage. At the same time, the actions undertaken initiated many debates, mainly in the circle of ethnologists, culturologists, animators or pedagogues. The voices of polemics touch upon many aspects of The Convention: from theoretical-methodological to those concerning particular means of realizing given tasks. The article concentrates on several selected issues that need reflection, or even, verification of opinions made so far. The findings in question are very important especially in the light of ratifying The Convention by the Republic of Poland in 2011.